New western Palaearctic Dinotrema species with mesoscutal pit and only medially sculptured propodeum (Hymenoptera, Braconidae, Alysiinae) - Munk, Thorkild (Pensoft Publishers, 2013)

(untitled)
Abstract. Descriptions of four new species of the genus Dinotrema Foerster with a mesoscutal pit and only medially sculptured propodeum are given. Dinotrema alysiae sp. n. (Denmark, England, Netherlands, Spain), Dinotrema paramicum sp. n. (Denmark, Finland), Dinotrema tirolense sp. n. (Italy) and Dinotrema valvulatum sp. n. (Denmark, Italy).